2017
DOI: 10.1038/s41467-017-02195-8
|View full text |Cite
|
Sign up to set email alerts
|

A 1-phytase type III effector interferes with plant hormone signaling

Abstract: Most Gram-negative phytopathogenic bacteria inject type III effector (T3E) proteins into plant cells to manipulate signaling pathways to the pathogen’s benefit. In resistant plants, specialized immune receptors recognize single T3Es or their biochemical activities, thus halting pathogen ingress. However, molecular function and mode of recognition for most T3Es remains elusive. Here, we show that the Xanthomonas T3E XopH possesses phytase activity, i.e., dephosphorylates phytate (myo-inositol-hexakisphosphate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 68 publications
2
57
0
Order By: Relevance
“…On the other hand, Liu et al (2011) showed that the Erwinia amylovora -derived elicitor HrpNEa activates the transcription factor MYB44, which in turn enhances the expression of EIN2 . Recently, Blüher et al (2017) demonstrated that Xanthomonas campestris pv. vesicatoria produces a type III secretion effector, XopH, that possesses phytase activity and modulates the Nicotiana benthamiana defense response.…”
Section: Zoom In: Et and Acc Regulate The Plant Immune And Symbiotic mentioning
confidence: 99%
“…On the other hand, Liu et al (2011) showed that the Erwinia amylovora -derived elicitor HrpNEa activates the transcription factor MYB44, which in turn enhances the expression of EIN2 . Recently, Blüher et al (2017) demonstrated that Xanthomonas campestris pv. vesicatoria produces a type III secretion effector, XopH, that possesses phytase activity and modulates the Nicotiana benthamiana defense response.…”
Section: Zoom In: Et and Acc Regulate The Plant Immune And Symbiotic mentioning
confidence: 99%
“…InsPs have been further implicated in plant immune signaling by the characterization of the Xanthomonas campestris effector protein XopH as phytase (InsP 6 phosphatase) (Bl€ uher et al, 2017). Ectopic expression of XopH in N. benthamiana indeed resulted in reduced InsP 6 , InsP 7 and InsP 8 concentrations (Bl€ uher et al, 2017).…”
Section: Inositol Pyrophosphate Signaling In Plantsmentioning
confidence: 99%
“…This is especially the case for phosphatases. Phosphatases have evolved across all living organisms and contribute to the regulation of diverse cellular functions (5, 6). A specific group of phosphatases named phytases can release phosphorus from phytic acid, which is one of the most important phosphorus reserves in plants and soils (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes are currently used in agroindustry to minimize P losses and to improve the levels of bioavailable P (14). A more recently described role of the phytases is their involvement in pathogenicity causing tissue damage in humans, coordination of the virulence program in Dickeya dadantii, and mediation of plant infection by Candida albicans and Xanthomonas , respectively (5, 15, 16).…”
Section: Introductionmentioning
confidence: 99%